KORELASI KONSENTRASI MALTODEKSTRIN TERHADAP SERBUK MINYAK IKAN KOMERSIAL DENGAN METODE FOAM-MAT FREZE DRYING - rukmana, jaka; Ikrawan, Yusep; Marthia, Nabila; Raphaella Shiffa, Amandita (Pasundan Food Technology Journal (PFTJ), 2025)
Milkfish oil (Chanos chanos) is a rich source of omega-3, but it is easily oxidized, requiring conversion into powder form to improve its stability. One effective method is Foam-Mat Freeze Drying, which utilizes maltodextrin as a foam stabilizer. This study was designed to evaluate the relationship between maltodextrin concentration and the quality attributes of commercial powdered milkfish oil, with the objective of developing a stable, reliable, superior, and use friendly formulation. The research method used was simple linear regression with a single factor of maltodextrin concentration (5%, 10%, 15%, and 20%). The study was divided into preliminary and main stages, with analyses including moisture content, fat content, peroxide value, omega 3-6-9 content, as well as color parameters (L*, a*, along with b*). Based on the results of the analysis results, a very strong and significant correlation was found with moisture content, peroxide value, omega-6 and omega-9 content, lightness (L*), and total color difference (∆E). Additionally, a very strong but not significant correlation was observed with fat content, omega-3 content, the red-green color coordinate (a*), and the yellow-blue color coordinate (b*). Further studies using different coating materials and additional analysis are recommended to comprehensively evaluate how the Foam-Mat Freeze Drying process influences on product quality.